Better Jobs in Central America : The Role of Human Capital - World Bank (Washington, DC, 2012)
The biggest challenge in terms of jobs in Central America is to create better conditions to stimulate more productive job creation in the context of a rapidly growing labor force. Overcoming this challenge will contribute to reducing poverty, inequality and social exclusion which are so entrenched in the Central American countries. To achieve this goal, Central America needs to address a two-pronged policy. First, the region must implement policies that help farmers and workers to move up the value chain, which means in some cases diversify the production structure by increasing the share of industry and services, and in other cases, it should improve the technological content and knowledge of existing activities to make them more productive (for example, agriculture). The paper is organized as follows: Section II describes the origin of the recent growth of the region and its impact on the labor market. Section III discusses the challenges of human capital faced by the region, and Sections IV and V provide governments with policy options for consideration.